Investment and Financial Constraints An Empirical Analysis of Norwegian Firms - Frode Johansen (Statistics Norway, Research Department, 1994)
This paper investigates the relationship between a firm's investment decision and its financial situation. We present a model of investment, where the cost of external finance is increasing in the debt ratio. The model is estimated using a panel of Norwegian manufacturing establishments for the period 1977-1990. The empirical analysis finds a positive relationship between a firm's debt ratio and its marginal return to capital. This indicates that firms with high debt ratios have higher costs of finance than other firms. Including convex adjustment costs in the model did not change this result, as the size of the adjustment costs was found to be very small.
Keywords: E22; G31; G32; 330; Investment; Financial markets; Panel data.